ADDITION OF MAGNESIUM (Mg) WITH ALUMINA (AL2O3) REINFORCER IN ALUMINUM MATERIAL COMPOSITES ON THE MECHANICAL PROPERTIES AND MICRO STRUCTURES - Widodo, Basuki; Sasmito , Agung Panji (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Aluminum is a widely used and applied material in daily life or in the industrial and automotive world. In order to improve the performance and properties of the application to be used, it needed an alloying element to improve the mechanical properties of the aluminum. Aluminum Matrix Composite (AMC) or better known as aluminum matrix composite is one type of material that has great potential to be developed, due to its good combination and properties such as high strength and hardness, low density, low density, capable of good machining, and its basic ingredients are easily found on the market and cheaper than other materials. This research was conducted using the stir casting process to be able to mix all the compositions contained in aluminum matrix composites and to help the distribution of alumina reinforcing particles (Al2O3) and aluminum matrices be evenly distributed. The parameters used in this casting process are varying the volume fraction of the Al2O3 amplifier by 0.5%; 1.5% and 2.5% plus the magnesium content remains 0.9%. The results showed that the addition of Al2O3 can increase the value of hardness and reduce the value of tensile strength. The highest hardness value was 75.3 HRB at the addition of Al2O3 by 2.5% and the lowest tensile strength value was 7.17 Kgf / mm2 with the percentage of Al2O3 addition of 0.5%.